Structural Understanding of Interleukin 6 Family Cytokine Signaling and Targeted Therapies: Focus on Interleukin 11 - Metcalfe, Riley D.; Putoczki, Tracy L.; Griffin, Michael D. W. (Frontiers in Immunology, 2020)
Cytokines are small signaling proteins that have central roles in inflammation and cell survival. In the half-century since the discovery of the first cytokines, the interferons, over fifty cytokines have been identified. Amongst these is interleukin (IL)-6, the first and prototypical member of the IL-6 family of cytokines, nearly all of which utilize the common signaling receptor, gp130. In the last decade, there have been numerous advances in our understanding of the structural mechanisms of IL-6 family signaling, particularly for IL-6 itself. However, our understanding of the detailed structural mechanisms underlying signaling by most IL-6 family members remains limited. With the emergence of new roles for IL-6 family cytokines in disease and, in particular, roles of IL-11 in cardiovascular disease, lung disease, and cancer, there is an emerging need to develop therapeutics that can progress to clinical use. Here we outline our current knowledge of the structural mechanism of signaling by the IL-6 family of cytokines. We discuss how this knowledge allows us to understand the mechanism of action of currently available inhibitors targeting IL-6 family cytokine signaling, and most importantly how it allows for improved opportunities to pharmacologically disrupt cytokine signaling. We focus specifically on the need to develop and understand inhibitors that disrupt IL-11 signaling.